Evaluasi Efektivitas Pendidikan Karakter Melalui Kegiatan Intrakurikuler Osis Di Sma Negeri 1 Muaro Jambi - Aris Munandar; Najwa Zahira; Alya Sefrina Zalmi; Agung Maulana; Elsa Herlinda; Asrillah Asrillah (Universitas Pakuan, 2026)
EVALUATION OF THE EFFECTIVENESS OF CHARACTER EDUCATION THROUGH INTRA-CURRICULAR STUDENT COUNCIL (OSIS) ACTIVITIES AT SMA NEGERI 1 MUARO JAMBI Character education is a fundamental element in shaping students’ personalities with noble character. However, the effectiveness of its implementation through intra-curricular programs still requires in-depth examination, as gaps are often found between conceptual objectives and practical implementation in the field. This study aims to evaluate the effectiveness of the OSIS intra-curricular program in developing students’ leadership character at SMA Negeri 1 Muaro Jambi by examining the alignment of program planning, quality of implementation, achievement of outcomes, as well as supporting and inhibiting factors. This research employs a qualitative approach with an evaluative design based on the CIPP model (Context, Input, Process, Product). Data were collected through direct observation, semi-structured interviews with the principal, vice principal for student affairs, OSIS advisors, OSIS administrators and members, as well as document analysis of program plans and activity reports. The findings indicate that the OSIS intra-curricular program is effective in fostering students’ leadership character through collaboratively designed program planning, experiential-based implementation, and continuous evaluation. The program has proven to cultivate values of responsibility, discipline, cooperation, and integrity, while also enhancing students’ managerial skills, communication abilities, and courage in decision-making. Supporting factors include school policy support, the commitment of supervising teachers, and a conducive school culture. Meanwhile, obstacles encountered consist of limited time due to academic workload, varying levels of student participation, and uneven teacher support. Overall, the OSIS intra-curricular program makes a significant contribution to strengthening students’ leadership character and has the potential to be adapted in other schools with adjustments to their respective contexts.